How Do Arts Programmes Contribute in International Development? A Systematic Review of Outcomes and Associated Processes. (April 2020) - Ware, Vicki-Ann; Dunphy, Kim
Arts programmes are increasingly utilised to support international development initiatives, supported by a nascent professional literature. This is occurring alongside a strengthening impetus for evidence-based and outcome-focussed development. This systematic review of the literature explored outcomes evidenced in arts-based development initiatives, and processes and artforms utilised to achieve these. From an initial pool of 67, 27 articles that included outcomes supported by data were analysed. Outcomes reported included inspiration of creativity, sharing of new ideas and skills, reconnection to traditional culture, improved social connections, promotion of health messages, healing and recovery from trauma and provision of new economic opportunities.